Pengaruh Penempatan Fasilitas Signage Terhadap Kepuasan Penumpang di Terminal Bandar Udara Internasional Kertajati - Muhammad Althaf; Awan Awan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
Kertajati International Airport is an international airport located in Majalengka Regency, West Java, this airport is still experiencing problems in the placement of signage that is less strategic. Based on the Minister of Transportation Regulation Number KM 22 Year 2005 and Appendix 9 Facilitation 2018, airport signs must be easy to understand and unobstructed. The application of these standards at the Kertajati International Airport Terminal is still not optimal, causing passenger confusion, especially in the departure area in finding routes after check-in. This study aims to determine the effect of signage placement on passenger satisfaction in finding routes at Kertajati Terminal and also to determine how much influence the placement of signage facilities has on passenger satisfaction at Kertajati International Airport. This research uses a descriptive statistical approach, which describes the numbers obtained from research and is described in the form of a systematic discussion. In this study, the data collection carried out was a survey method using a questionnaire (questionnaire). The survey method used is by distributing questionnaires to passengers directly in the Domestic Departure area at Kertajati International Airport. The data analysis techniques used are validity test, reliability test, simple linear regression test, T test and coefficient of determination (R2) test. Based on the results of analysis and discussion and data processing on the variable placement of signage facilities (X) on passenger satisfaction (Y), it is decided that the significant value obtained is 0.000, which means it is smaller or less than (<) 0.05, it can be concluded that the placement of signage facilities has a significant effect on passenger satisfaction at the Kertajati International Airport Terminal. The magnitude of the value of the effect of the placement of signage facilities on passenger satisfaction is known that the number obtained for the variable placement of signage facilities is 65.9% of the passenger satisfaction variable.